Characteristic Analysis and Simulated Test of Hybrid Bearing with the Introduction of Piezoelectric Controller - Runlin Chen; Wu Ouyang; Zhaoyang Shi; Yangyang Wei; Xiaoyang Yuan (Shock and Vibration)
A novel hybrid bearing with the introduction of piezoelectric controller and tilting pads to control vibration actively is proposed in this paper, and the feasibility of this scheme is verified by theoretical calculation and experimental data. This scheme can control the vibration of bearing actively by using the electromechanical characteristics of piezoelectric ceramic transducer (PZT) components. The static internal character of PZT and static external characteristic of piezoelectric control component are analyzed, and the calculation equations of preload coefficient and driving force of the new bearing are given. The simulation setup of the new bearing is designed and developed. The data representing the relationship of displacement of pad pivot, driving force, voltage, and the simulation stiffness of liquid film are obtained in the test, and the feature parameters of piezoelectric control component are amended to analyze the relationship between preload coefficient of the bearing and driving voltage. The proposed new bearing has the function of controlling preload actively. The theoretical and experimental research results provide essential guidance for the detail design of this new bearing and also provide a new idea for the vibration control of high speed rotor systems.